“Do We Not Bleed?” Sanitation, Menstrual Management, and Homelessness in the Time of COVID - Teizazu, Hawi; Sommer, Marni; Gruer, Caitlin; Giffen, David; Davis, Lindsey; Frumin, Rachel; Hopper, Kim (Columbia Journal of Gender and Law, 2021)
Although access to adequate sanitation is formally recognized as a basic human right, public toilets have long been flagged as absent necessities by groups marginalized by class, gender, race, and ability in the United States. Navigating public spaces without the guarantee of reliable restrooms is more than a passing inconvenience for anyone needing immediate relief. This includes workers outside of traditional offices, people with medical conditions, caretakers of young children, or anyone without access to restroom amenities provided to customers. This absence is also gendered in ways that constrain the freedom of those who menstruate to participate in the public sphere. Managing menstrual hygiene requires twenty-four-hour access to safe, clean facilities, equipped for washing blood off hands and clothing and mechanisms for discreet disposal of used menstrual products. Public provision of such amenities is woefully inadequate in New York City (NYC), and homeless women especially bear the brunt of that neglect. Public health concerns about open defecation, coupled with feminist complaints that their absence restricted women’s ability to be out in public, catalyzed state investment to construct public toilets in the late 1800s. By 1907, eight had been built in NYC near public markets, and by the 1930s, the city built and renovated 145 comfort stations. However, changing public perceptions, vandalism, maintenance costs, and the City’s fiscal crisis in the 1970s all combined to reduce their numbers and degrade their quality. Public pay toilets provided a brief respite before falling victim to protest by feminists, who were rightly dismayed by policies that required payments for public usage of toilets but not for urinals. Supply deteriorated, and by 2019, NYC ranked ninety-third among large U.S. cities in per capita provision of public toilets. The remaining facilities are inadequately maintained and poorly monitored. The absence of public toilets poses an everyday challenge, but public health emergencies bring the need for public toilets into clear focus––as seen during the COVID-19 pandemic, which eliminated publicly accessible bathrooms in both private and public settings. That said, the effects of COVID on bathroom availability disproportionately affected those who were unable to heed the public health message to shelter at home––mobile “essential workers” and individuals experiencing homelessness. Homelessness advocates have long complained that civic toilet scarcity amounts to de facto entrapment, turning biological necessities into “public nuisances” for want of appropriate facilities. Criminalizing public urination and defecation in the absence of public facilities punishes the existence of individuals experiencing homelessness and challenges outreach workers’ efforts to gain their trust. With women increasingly prominent among those living on the streets or in shelters, this scarcity also impedes managing menstruation. Default reliance on private business is no answer for anyone defying passable “customer” profiles. Nor does the recent success of NYC’s “menstrual equity” efforts in schools, prisons, and shelters, with their primary focus on supplying menstrual products, suffice to cover the daytime needs of those on the move.